Practice of Arabic speaking skill learning strategies: A study on B.A.R AND I.R.K. students at Centre for Foundation Studies (CFS), IIUM - Arshad, Mastura; Abu Bakar, Kaseh; Hashim, Marzidah; Raja Sulaiman, Raja Munirah; Muhammad, Norasmazura (2013)
Language skills is often associated with the use of learning strategies. Studies found that the use of appropriate and effective strategies can enhance students’ speaking skill. Thus, this research explores the practice and knowledge of Arabic Speaking Skill Learning Strategies among Malay students at the Centre for Foundation Studies (CFS) IIUM, to identify the relationship between the achievement in APT Skills Test and the strategies being practiced, and to identify the factors in the practiced strategies. This study divides speaking skill learning strategies into in-classroom, use of media, participation in co-curricular activities, speaking with partners and individual strategies. This research involves 163 respondents taking B.A.R. and I.R.K. courses, using the Cluster Sampling Method. Questionnaire is used to collect data for this study and is confirmed by three experts. Cronbach Alpha reliability level of the questionnaire is high (0.7). The data are analyzed through descriptive and inferential analysis, using mean, standard deviation, percent, Chi-Square Test, and Multiple Regression Analysis. The findings show that the level of the practiced strategies is moderate while the most unknown strategy category to the students is the Self Learning Strategy. Inferential data analysis shows that there is a positive relationship between the achievement of APT Skills Test, and the use of media strategy and the use of self-learning strategy. In addition, the demographic factors such as gender, achievement in APT Skills Test, Arabic language learning background and learning period are not the factors in the practice of Arabic Speaking Skill Learning Strategies.